Принципи правового мислення - Андрюшко, І.Я.; Андрюшко, И. Я.; Andrjushko, I. (My University, 2012)
In this article principles of the legal thinking are studied by means of analysis of connections between the features of the legal thinking and principles of the legal thinking, principles of right and legal principles, and also descriptions of such principles of the legal thinking, as principles of deﬁ niteness of the legal thinking, sequence of the legal thinking, validity of the legal thinking.
Андрюшко І. Я. Принципи правового мислення / І. Я. Андрюшко // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2012. – Вип. 45. – С. 14-21.
Keywords: правове мислення; принципи правового мислення; принципи права; правовое мышление; принципы правового мышления; принципы права; legal thinking; the principles of legal thinking; principles of law